2022
DOI: 10.1109/access.2022.3199691
|View full text |Cite
|
Sign up to set email alerts
|

Toward Autonomous Vehicles and Machinery in Mill Yards of the Forest Industry: Technologies and Proposals for Autonomous Vehicle Operations

Abstract: The use of autonomous systems on the wood processing sites of forest industries can significantly increase safety, productivity, and efficiency by reducing the number of monotonous and dangerous tasks conducted by human labor utilizing heavy machinery. However, autonomous machines are challenging and difficult to implement in the mill yards environment because of the dynamic and complex working environment, and partly unstructured processes. The inherent complexity of wood handling and storage tasks is requiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 70 publications
(114 reference statements)
0
8
0
Order By: Relevance
“…In this case, if the high demand for sustainable warehousing comes from the government, policymakers, producers, or even end customers, warehousing companies should be prepared and know what to do, why, and when. One potential higherlevel integration of automatization optimization in the WMS context could be self-operating autonomous vehicles [92] in the restricted parts of warehouses and their surrounding yards to be controlled by the WMS. In the long term, WMS could be developed to handle largerscale fleets [93,94], and improve their optimization capabilities in warehouse environments.…”
Section: Future Research Suggestionsmentioning
confidence: 99%
“…In this case, if the high demand for sustainable warehousing comes from the government, policymakers, producers, or even end customers, warehousing companies should be prepared and know what to do, why, and when. One potential higherlevel integration of automatization optimization in the WMS context could be self-operating autonomous vehicles [92] in the restricted parts of warehouses and their surrounding yards to be controlled by the WMS. In the long term, WMS could be developed to handle largerscale fleets [93,94], and improve their optimization capabilities in warehouse environments.…”
Section: Future Research Suggestionsmentioning
confidence: 99%
“…According to Lundbäck (2022), autonomous loading has a higher economic potential than autonomous driving during forwarding work, since loading is the most time consuming work element. Another advantage of autonomous systems in forestry is the potential to increase safety, by reducing dangerous tasks performed by human operators of heavy machinery (Abdelsalam et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a research done in India has reported that up to 37% of the overall losses in seed yield of paddy are caused by uncontrolled weed growth [7], among a host of other challenges. Therefore, it could be seen that there are huge gaps of enablement through technology that could be explored in this domain for the betterment of society, and remote sensing is a key component due to the sheer scale and coverage required in agriculture, e.g., like water usage and lost preventive systems [8], industry scale autonomous vehicles [9] and IoT based solutions with humanitarian thoughts [10] and so on.…”
Section: Introductionmentioning
confidence: 99%